An XML document warehouse model - Nassis, V.; Dillon, Tharam S.; Rajugan, Rajagopal; Rahayau, W. (Springer-Verlag, 2006)
EXtensible Markup Language (XML) has rapidly gained importance as a mechanism for the exchange of information amongst heterogeneous sources over the web. In order to deal with the challenging task of managing the large volumes of data appearing, encoded in XML transactional databases, the need to explore the XML Document Warehouse (XDW) approach is initiated. The applications of the Requirement Engineering (RE) process and Object-Oriented conceptual models have proven their usefulness in building successful software models and solutions. In this paper we introduce an integration methodology for the development of XDWs. Initially we provide a formal notation of the structural design for the XDW conceptual model. Secondly we focus on deriving requirements for the XDWs by exploring the Goal-Question Metric (GQM) approach. We adapt and extend this concept to XDWs and introduce a method for developing warehouse requirements considering user viewpoints and organizational objectives. The implementation of our proposed warehouse requirement derivation model is demonstrated using a case study example extracted from a simplified real-world scenario.